Enhancing the structural diversity between forest patches—A concept and real‐world experiment to study biodiversity, multifunctionality and forest resilience across spatial scales - Jörg Müller; Oliver Mitesser; Marc W. Cadotte; Fons van der Plas; Akira S. Mori; Christian Ammer; Anne Chao; Michael Scherer‐Lorenzen; Petr Baldrian; Claus Bässler; Peter Biedermann; Simone Cesarz; et al. (Global Change Biology, 2023)
Intensification of land use by humans has led to a homogenization of landscapes and decreasing resilience of ecosystems globally due to a loss of biodiversity, including the majority of forests. Biodiversity–ecosystem functioning (BEF) research has provided compelling evidence for a positive effect of biodiversity on ecosystem functions and services at the local (α‐diversity) scale, but we largely lack empirical evidence on how the loss of between‐patch β‐diversity affects biodiversity and multifunctionality at the landscape scale (γ‐diversity). Here, we present a novel concept and experimental framework for elucidating BEF patterns at α‐, β‐, and γ‐scales in real landscapes at a forest management‐relevant scale. We examine this framework using 22 temperate broadleaf production forests, dominated by Fagus sylvatica . In 11 of these forests, we manipulated the structure between forest patches by increasing variation in canopy cover and deadwood. We hypothesized that an increase in landscape heterogeneity would enhance the β‐diversity of different trophic levels, as well as the β‐functionality of various ecosystem functions. We will develop a new statistical framework for BEF studies extending across scales and incorporating biodiversity measures from taxonomic to functional to phylogenetic diversity using Hill numbers. We will further expand the Hill number concept to multifunctionality allowing the decomposition of γ‐multifunctionality into α‐ and β‐components. Combining this analytic framework with our experimental data will allow us to test how an increase in between patch heterogeneity affects biodiversity and multifunctionality across spatial scales and trophic levels to help inform and improve forest resilience under climate change. Such an integrative concept for biodiversity and functionality, including spatial scales and multiple aspects of diversity and multifunctionality as well as physical and environmental structure in forests, will go far beyond the current widely applied approach in forestry to increase resilience of future forests through the manipulation of tree species composition.